2018
DOI: 10.1002/cjas.1496
|View full text |Cite
|
Sign up to set email alerts
|

How Does Legitimacy Operate in Emerging Capital Markets? Investigating the Moderating Effects of Premium Listings and Firm Size on Risk

Abstract: Drawing on an institutional theoretical perspective, we investigate the impact of the origins of organizational legitimacy on systematic risk using a sample of 358 Brazilian companies between the years 2002 and 2007. We regard three origins of legitimacy—formal–regulatory (presence in premium listings), cultural–cognitive (board of directors), and normative legitimacy (reputation)—to empirically investigate how a company's size and adherence to premium lists moderate other sources of legitimacy. Our results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 70 publications
(199 reference statements)
2
21
0
Order By: Relevance
“…He points out that such ties have the capacity to extract valuable resources from the environment. In Brazil, Rossoni and Mendes-DaSilva [51] and Rossoni and Machado-Da-Silva [37] used the proportion of nonredundant ties as one of the indicators of the legitimacy of the board. Rossoni et al [50], using board's social capital ideas, showed that heterogeneous relational resources have a stronger and more significant influence than the resources available from board's direct ties.…”
Section: Hypothesis 1amentioning
confidence: 99%
See 2 more Smart Citations
“…He points out that such ties have the capacity to extract valuable resources from the environment. In Brazil, Rossoni and Mendes-DaSilva [51] and Rossoni and Machado-Da-Silva [37] used the proportion of nonredundant ties as one of the indicators of the legitimacy of the board. Rossoni et al [50], using board's social capital ideas, showed that heterogeneous relational resources have a stronger and more significant influence than the resources available from board's direct ties.…”
Section: Hypothesis 1amentioning
confidence: 99%
“…The first theoretical understanding has to do with the positioning of the board and its effects on the performance of companies. Various studies use positioning measures of a player in the network to test their research hypotheses or questions, such as small world studies, developed by Brookfield et al [27], Mendes-Da-Silva [49], and Pusser et al [67], who studied interlocking between company boards and American universities, or Rossoni and Machado-Da-Silva [37] and Rossoni and Mendes-Da-Silva [51], in their research into legitimacy and market value in companies quoted on the B3. This study produces evidence that the board and owners relational resources have more effect than only board relational position on the cost of capital [39,50].…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, the Novo Mercado has the highest level of corporate governance in the Brazilian capital market (Monte, Rezende, Teixeira, & Besarria, 2010; Dalmácio, Lopes, Rezende, & Sarlo Neto, 2013; Martins & Paulo, 2014; Rossoni & Mendes‐Da‐Silva, 2018). This is an important motivation for choosing this level as the highest standard of governance in Brazil, especially, as it is optional and has the largest number of practices to be adopted by companies.…”
Section: Introductionmentioning
confidence: 99%
“…This study does not address the analysis of corporate governance practices as risk factors, we take a look at the listing phenomenon at the highest level of corporate governance of B 3 and its association with risk (Rossoni & Mendes‐Da‐Silva, 2018) and return on investment (Fuenzalida, Mongrut, Arteaga, & Erausquin, 2013). We address the fact that such listing has played an important role in legitimizing firms (Jonsson, 2020), particularly in information environments with low legal protection for investors, as usually occurs in emerging countries.…”
Section: Introductionmentioning
confidence: 99%